THE ROLE OF INTERCULTURAL COMMUNICATION IN ENHANCING STUDENTS' READING LITERACY IN THE INDONESIAN EFL CONTEXT - Asra, Surya; Rahmiati, Rahmiati; Fadlia, Fadlia; Mawaddah, Aina (Universitas Islam Sumatera Utara (UISU), 2025)
Students’ reading skills in English reflect the cultural interaction that takes place during language learning. When students are able to recognize and understand the cultural aspects of a text, it is predicted that they can usually interpret it more effectively. The purpose of this study is to examine students’ understanding of intercultural communication in English reading and to investigate the relationship between intercultural communication and reading comprehension. The study applied a quantitative descriptive method, using a reading comprehension test and a questionnaire as the instruments for data collection. The participants consisted of 40 high school students, equally divided into 20 males and 20 females. The findings indicate a strong and positive correlation between students’ intercultural communication skills and their ability to comprehend English reading texts. The linear regression analysis produced a strong correlation coefficient (R2 = 0.64) by referring to Correlation Pearson Product Moment. These findings suggest that English teachers should consider the intercultural communication in teaching reading comprehension. Eventually, incorporating intercultural communication into English language teaching is essential, particularly to support the development of students’ reading skills.